Developing a Graduate Level Embedded System Programming Course Content by Using Blended Programming Methodologies: Text-Based and Graphical - (:unkn) unknown (IEEE, 2014)
This article deals with identifying the materials and the methods that will be used in this course based on Embedded System Programming (ESP) course for Electrical-Electronics Engineering Graduate program of MU Faculty of Technology. When the varying levels of skill and knowledge of the students is considered, it becomes necessary to adopt a blended programming method for the contents of the course. Even though the course is regarded as 3+0 ECTS of 8 credits (Theory: 3, Applied: 0), a content supported with extensive application is recommended. The content of the course allows developing applications using Xilinx Spartan 3E Starter Kit. Students taking this course are able to choose a method best fitted to their programming skills or preferences. However, it might be possible that the lecturer may not have a wide range of programming knowledge and skills. In this case, the graduate students are expected to determine and complete their own needs or shortcomings with the accumulation of knowledge they gained in their undergraduate studies. With the lecturer's guidance, the students are free to choose whether to use graphical programming (LabVIEW, LabVIEW FPGA Module) or conventional text-based programming (Verilog, VHDL, Matlab HDL Coder) in their projects. In this way, we expect an improvement in understanding of the contents and an expansion in scope.
Keywords: Embedded system programming; FPGAs; HDL; Verilog; LabVIEW FPGA Module; Xilinx ISE